Three new chondrosarcoma cell lines: one grade III conventional central chondrosarcoma and two dedifferentiated chondrosarcomas of bone - van Oosterwijk, Jolieke G (BioMed Central, 2012)
BACKGROUND: Chondrosarcoma is the second most common primary sarcoma of bone. High-grade conventional chondrosarcoma and dedifferentiated chondrosarcoma have a poor outcome. In pre-clinical research aiming at the identification of novel treatment targets, the need for representative cell lines and model systems is high, but availability is scarce. METHODS: We developed and characterized three cell lines, derived from conventional grade III chondrosarcoma (L835), and dedifferentiated chondrosarcoma (L2975 and L3252) of bone. Proliferation and migration were studied and we used COBRA-FISH and array-CGH for karyotyping and genotyping. Immunohistochemistry for p16 and p53 was performed as well as TP53 and IDH mutation analysis. Cells were injected into nude mice to establish their tumorigenic potential. RESULTS: We show that the three cell lines have distinct migrative properties, L2975 had the highest migration rate and showed tumorigenic potential in mice. All cell lines showed chromosomal rearrangements with complex karyotypes and genotypic aberrations were conserved throughout late passaging of the cell lines. All cell lines showed loss of CDKN2A, while TP53 was wild type for exons 5–8. L835 has an IDH1 R132C mutation, L2975 an IDH2 R172W mutation and L3252 is IDH wild type. CONCLUSIONS: Based on the stable culturing properties of these cell lines and their genotypic profile resembling the original tumors, these cell lines should provide useful functional models to further characterize chondrosarcoma and to evaluate new treatment strategies.